Repeated remote ischemic conditioning attenuates left ventricular remodeling via exosome-mediated intercellular communication on chronic heart failure after myocardial infarction. (15th January 2015) - Yamaguchi, Takehiro; Izumi, Yasukatsu; Nakamura, Yasuhiro; Yamazaki, Takanori; Shiota, Masayuki; Sano, Soichi; Tanaka, Masako; Osada-Oka, Mayuko; Shimada, Kenei; Miura, Katuyuki; Yoshiyama, Minoru; Iwao, Hiroshi
Abstract: Background: Remote ischemic conditioning (RIC) by repeated treatment of transient limb ischemia is a clinically applicable method for protecting the heart against injury at the time of reperfusion. In this study, we investigated the effects of repeated RIC on cardiac dysfunction after myocardial infarction (MI). Methods and results: At 4 weeks after MI, rats were separated into the untreated (UT) group or the RIC-treated group. RIC treatment was performed by 5 cycles of 5 min of bilateral hindlimb ischemia and 5 min of reperfusion once a day for 4 weeks. Despite comparable MI size, left ventricular (LV) ejection fraction (LVEF) was significantly improved in the RIC group compared with the UT group. Furthermore, the LVEF in the RIC group was improved, although not significantly, after treatment. RIC treatment also prevented the deterioration of LV diastolic function. MI-induced LV interstitial fibrosis in the boundary region and oxidant stress were significantly attenuated by RIC treatment. MicroRNA-29a (miR-29a), a key regulator of tissue fibrosis, was highly expressed in the exosomes and the marginal area of the RIC group. Even in the differentiated C2C12-derived exosomes, miR-29a expression was significantly increased under hypoxic condition. As well as miR-29a, insulin-like growth factor 1 receptor (IGF-1R) was highly expressed both in the exosomes and remote non-infarcted myocardium of the RIC group. IGF-1R expression was also increased in the C2C12-derived exosomes under hypoxic conditions. Conclusions: Repeated RIC reduces adverse LV remodeling and oxidative stress by MI. Exosome-mediated intercellular communication may contribute to the beneficial effect of RIC treatment. Highlights: Repeated remote ischemic conditioning (RIC) is useful for chronic heart failure (HF). RIC increases the total amount of proteins secreted from exosomes. RIC prevents cardiac dysfunction via exosome-mediated intercellular communication. RIC is easy to perform and may be well tolerated to the patients with chronic HF.